2015
DOI: 10.1002/micr.22395
|View full text |Cite
|
Sign up to set email alerts
|

Immediate nipple reconstruction with thoracodorsal artery perforator flap in breast reconstruction by latissimus dorsi myocutaneous flap in patients with Poland's syndrome

Abstract: Loss of long-term projection is the major disadvantage of nipple reconstruction using local flaps. We report a technique of immediate perforator flap nipple reconstruction in breast reconstruction by latissimus dorsi (LD) myocutaneous flap in patients with Poland's syndrome. From March 2007 to July 2012, 12 female patients (age range, 15-21 years) underwent breast reconstructions and immediate nipple reconstructions. A thoracodorsal artery perforator (TAP) flap was simultaneously raised on the LD muscle flap a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Patient satisfaction with BR is an issue of clinical interest. Objective assessment of aesthetic outcomes including breast size, shape, symmetry, skin color, and scarring, have been used in both Chinese and Western studies to determine the effectiveness of BR [ 23 25 ]. However, satisfaction from patient perspective is not on the basis of technical success of the surgery alone, but on a range of psychosocial factors and individual experience [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient satisfaction with BR is an issue of clinical interest. Objective assessment of aesthetic outcomes including breast size, shape, symmetry, skin color, and scarring, have been used in both Chinese and Western studies to determine the effectiveness of BR [ 23 25 ]. However, satisfaction from patient perspective is not on the basis of technical success of the surgery alone, but on a range of psychosocial factors and individual experience [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with previous studies that have reported high success rates and patient satisfaction with the pedicled perforator flap technique for initial nipple reconstruction. 18,19 The favorable outcomes and high patient satisfaction rates in this study suggest that this technique has the potential to become a preferred method for salvage nipple reconstruction.…”
Section: Discussionmentioning
confidence: 84%
“…Через 2 месяца был выполнен второй этап -удаление экспандера и установка имплантата необходимого размера. Данная мето-дика была применена у 12 пациенток в возрасте от 15 до 21 года, при этом хорошие и очень хорошие результаты были отмечены в 11 случаях [42].…”
Section: реконструктивные вмешательства на грудной клеткеunclassified